Retrospective analysis of 300 microbial cell-free DNA sequencing results in routine blood stream infection diagnostics - Claudio Neidhöfer; Claudio Neidhöfer; Niklas Klein; Niklas Klein; Aylin Yürüktümen; Tessa Hattenhauer; Rebekka Mispelbaum; Christian Bode; Tobias A. W. Holderried; Achim Hoerauf; Marijo Parčina (Frontiers in Cellular and Infection Microbiology)
IntroductionBloodstream infections are a critical challenge worldwide due to the slow turnaround time of conventional microbiological tests for detecting bacteremia in septic patients. Noscendo GmbH (Duisburg, Germany) has developed the CE/IVD pipeline DISQVER for clinical metagenomics testing based on cell-free DNA (cfDNA) from blood samples to address this issue.MethodsWe conducted a retrospective study to evaluate the diagnostic utility of this methodological setup in improving treatment decisions since it was introduced into our clinical setting. Between January 2021 and June 2022, the first 300 cases in which DISQVER was applied at our university hospital were collected and analyzed. The results were compared with routine microbiology test results, clinical picture, associated treatment decisions, and clinical course.ResultsOur findings demonstrate that DISQVER results where no pathogen was reported effectively ruled out bacterial bloodstream infections, whereas positive results varied in their usefulness. While the metagenomic approach proved highly valuable for detecting non-culturable and rare pathogens, its utility was limited in cases where detected microorganisms were commonly associated with the microbiota.DiscussionPerforming on-site analysis might mitigate delays resulting from logistical challenges and might help optimizing antibiotic stewardship. Once prompt results can be obtained, the relevance of incorporating molecular resistograms will become more pronounced. Further, the specific patient subgroups that most benefit from this analysis must be worked out. Guiding clinicians in identifying the infection focus based on the detected bacteria would significantly improve patient care. Lastly, evidence of filamentous fungi must be diligently followed up.